Social Media Use for Health Communication by the CDC in Mainland China: National Survey Study 2009-2020 - Zeng, Runxi (J Med Internet Res, 2020)
BACKGROUND: In recent years, public health incidents that pose a serious threat to public life have occurred frequently in China. The use of social media by public health authorities has helped to reduce these threats by increasing effective risk communication between the government and the public. OBJECTIVE: The aim of this study is to reveal how China’s Center for Disease Control and Prevention (CDC) uses social media to improve three aspects of health communication between the government and the public: adoption, operation, and interaction. METHODS: To analyze the 134 CDC government Weibo accounts at the provincial- and prefecture-level administration regions in mainland China, we collected their account data and extracted 1215 Weibo tweets. We also supplemented the data to reveal the overall performance of the CDC’s government Weibo use during the COVID-19 crisis. RESULTS: The registration rate of the CDC’s government Weibo accounts increased year by year, and the local authorities registered Weibo accounts before the central government authorities. In total, 29.8% (n=134) of the 450 CDC facilities have registered an account. Among the 134 CDC facilities that have registered Weibo accounts, the registration rate in the eastern region (n=68, 50.7%) was higher than those in the central region (n=30, 22.4%) and the western region (n=36, 26.9%). Nearly 90.0% of these Weibo accounts had official certification, but there were dropouts in the specific operating process. One-third of the accounts have not been updated for more than 1 year, and the number of Weibo followers was polarized, with a maximum and minimum difference of 1 million. The response rate to users’ comments was less than 1%. Emergency information, multimedia content, and original content were more helpful in promoting communication between the government and the public. Such interaction was partially improved during the COVID-19 pandemic. The CDC updated the daily epidemic situation and provided popular science information for epidemic prevention and control for the public in a timely manner. CONCLUSIONS: China’s CDC is using more social media to popularize daily health information and has taken the first step to improve communication between the government and the public. However, equal dialogue, two-way interactions, and effective communication with the public still need improvement.